Herschel observations of the circumstellar environments of the Herbig Be stars R Mon and PDS 27 - Jiménez-Donaire, Maria Jesús (Astronomy and astrophysics, 2017)
Context. The circumstellar environments of Herbig Be stars in the far-infrared are poorly characterised, mainly because they are often embedded and rather distant. The analysis of far-infrared spectroscopy allows us to make a major step forward by covering multiple rotational lines of molecules, e.g. CO, that are useful probes of the physical conditions of the gas.Aims. We characterise the gas and dust in the discs and environments of Herbig Be stars, and we compare the results with those of their lower-mass counterparts, the Herbig Ae stars.Methods. We report and analyse far-infrared observations of two Herbig Be stars, R Mon and PDS 27, obtained with the Herschel instruments PACS and SPIRE. We construct spectral energy distributions and derive the infrared excess. We extract line fluxes from the PACS and SPIRE spectra and construct rotational diagrams in order to estimate the excitation temperature of the gas. We derive CO, [O I] and [C I] luminosities to determine the physical conditions of the gas, and the dominant cooling mechanism.Results. We confirm that the Herbig Be stars are surrounded by remnants from their parental clouds, with an IR excess that mainly originates in a disc. In R Mon we detect [O I], [C I], [C II], CO (26 transitions), water and OH, while in PDS 27 we only detect [C I] and CO (8 transitions). We attribute the absence of OH and water in PDS 27 to UV photo-dissociation and photo-evaporation. From the rotational diagrams, we find several components for CO; we derive Trot949 ± 90 K, 358 ± 20 K and 77 ± 12 K for R Mon; 96 ± 12 K and 31 ± 4 K for PDS 27; and 25 ± 8 K and 27 ± 6 K for their respective compact neighbours. The forsterite feature at 69 μm was not detected in either of the sources, probably due to the lack of (warm) crystalline dust in a flat disc. We find that cooling by molecules is dominant in the Herbig Be stars, while this is not the case in Herbig Ae stars where cooling by [O I] dominates. Moreover, we show that in the Herbig Be star R Mon, outflow shocks are the dominant gas heating mechanism, while in Herbig Ae stars it is stellar.Conclusions. The outflow of R Mon contributes to the observed line emission by heating the gas in the central spaxel/beam covering the disc and in the immediate surroundings, as well as in those spaxels/beams covering the parabolic shell around it. PDS 27, a B2 star, has dispersed a large part of its gas content and/or destroyed molecules; this is likely given its intense UV field.